Network centric warfare and coalition operations the new military operating system - Mitchell, Paul T. (Routledge contemporary security studies, 2009)
Argues that Network Centric Warfare (NCW) influences how developed militaries operate in the same fashion that an operating system influences the development of computer software. This book examines the military power of the US; the influence of NCW on military thinking; and, the centrality of coalition operations in modern military endeavours.